2010
DOI: 10.1177/0363546510370197
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of the Relationship between Lower Body Stiffness and Hamstring Injury in Professional Australian Rules Footballers

Abstract: It appears that a high bilateral hamstring stiffness and leg stiffness may be a determinant in the risk of sustaining a hamstring injury. Further, relatively lower hamstring stiffness in the involved limb of injured players appears to be associated with increased injury and may be related to a lack of strength. The information from stiffness assessment may allow medical staff to determine the hamstring risk status for individual players in team sports.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
157
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(175 citation statements)
references
References 43 publications
(84 reference statements)
3
157
2
1
Order By: Relevance
“…(37) Interestingly, the frequency of physiotherapy sessions did not affect the DRP in our study. Contrary to our findings,…”
Section: International Association Of Athletics Federations Worldcontrasting
confidence: 46%
“…(37) Interestingly, the frequency of physiotherapy sessions did not affect the DRP in our study. Contrary to our findings,…”
Section: International Association Of Athletics Federations Worldcontrasting
confidence: 46%
“…Watsford et al 52 demonstrated prospectively that individuals who sustained acute hamstrings strain injuries had greater hamstrings stiffness than an uninjured cohort. However, whereas the bilateral average hamstrings stiffness differed between groups, that of the injured limb was not different from the uninjured group.…”
Section: Summary and Clinical Applicationmentioning
confidence: 99%
“…Since the majority of the injuries in ARF are to the lower-limbs, and particularly hamstrings, this region has been the focus of several studies attempting to discover modifiable, intrinsic injury risk factors. The potential risk factors for hamstring injuries that have been investigated include strength [32,45,46], flexibility [34,39,45,47], movement discrimination ability [46] and musculotendinous stiffness [40]. During a game of ARF the hamstring muscles may experience high forces during sprinting, kicking and jumping, as well as lunging for the ball.…”
Section: Modifiable Intrinsic Risk Factorsmentioning
confidence: 99%
“…Stiffness of the hamstrings can be determined using the free oscillation technique where a perturbation is applied to the limb maintained in a static contraction and the resultant oscillation is recorded by an accelerometer attached to the distal lower-limb. Lower- limb stiffness, which includes contributions from joint structures, bones as well as musculotendinous units, can be determined using a unilateral hopping test on a force platform to record the displacement of the centre of mass and the ground reaction forces [40]. It has been found that high bilateral lower-limb stiffness, as well as high bilateral hamstring stiffness, increased the risk of hamstring injuries in professional footballers, but bilateral difference was not shown to be a risk factor in this study [40].…”
Section: Modifiable Intrinsic Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation